Applied urban ecology : a global framework - Richter, Matthias, 1964-; Weiland, Ulrike; Wiley InterScience (Online service) (Oxford ; Hoboken, NJ : Wiley-Blackwell, 2012)
Applied Urban Ecology: A Global Framework explores ways in which the environmental quality of urban areas can be improved starting with existing environmental conditions and their dynamics. Written by an internationally renowned selection of scientists and practitioners, the book covers a broad range of established and novel approaches to applied urban ecology. Approaches chosen for the book are placed in the context of issues such as climate change, green- and open-space development, flood-risk assessment, threats to urban biodiversity, and increasing environmental pollution (especially in the "megacities" of newly industrialized countries). All topics covered were chosen because they are socially and socio-politically relevant today. Further topics covered include sustainable energy and budget management, urban water resource management, urban land management, and urban landscape planning and design. Throughout the book, concepts and methods are illustrated using case studies from around the world. A closing synopsis draws conclusions on how the findings of urban ecological research can be used in strategic urban management in the future. Applied Urban Ecology: A Global Framework is an advanced textbook for students, researchers and experienced practitioners in urban ecology and urban environmental research, planning, and practice.
Front Matter -- Introduction. Urban EcologyBrief History and Present Challenges / Ulrike Weiland, Matthias Richter -- Urban Ecology: Related Disciplines and Methods. ThematicMethodical Approaches to Applied Urban Ecology / Matthias Richter, Ulrike Weiland -- Monitoring Urban Land use Changes with Remote Sensing Techniques / Ellen Banzhaf, Maik Netzband -- Selected Fields of Urban Ecology. Quantifying Spatiotemporal Patterns and Ecological Effects of Urbanization: A Multiscale Landscape Approach / Jianguo Wu, Alexander Buyantuyev, G Darrel Jenerette, Jennifer Litteral, Kaesha Neil, Weijun Shen -- Designing Urban Systems: Ecological Strategies with Stocks and Flows of Energy and Material / Peter Baccini -- Environmental and Ecological Threats in Indian Mega-Cities / Surinder Aggarwal, Carsten Butsch -- From Wasteland to Wilderness Aspects of a New Form of Urban Nature / Dieter Rink, Harriet Herbst -- Multiscale Flood Risk Assessment in Urban Areas A Geoinformatics Approach / Norman Kerle, Dinand Alkema -- Urban Open Spaces and Adaptation to Climate Change / Marialena Nikolopoulou -- Social Aspects of Urban Ecology in Developing Countries, with an Emphasis on Urban Domestic Gardens / Sarel Cilliers, Stefan Siebert, Elandrie Davoren, Rina Lubbe -- Plant Material for Urban Landscapes in the Era of Globalization: Roots, Challenges and Innovative Solutions / Maria Ignatieva -- Ecological Infrastructure Leads the Way: The Negative Approach and Landscape Urbanism for Smart Preservation and Smart Growth / Kongjian Yu -- Integrating Science and Creativity for Landscape Planning and Design of Urban Areas / Antje Stokman, Christina von Haaren -- Landscape as a Living System: Shanghai 2010 Expo Houtan Park / Kongjian Yu -- Geographical Perspectives on a Radical Political Ecology of Water / Alex Loftus -- Synthesis. Synthesizing Urban Ecology Research and Topics for Urban Environmental Management / Matthias Richter, Ulrike Weiland -- Index.
Includes bibliographical references and index.
Keywords: Urban ecology (Biology); Applied ecology; Applied ecology; Urban ecology (Biology); Electronic resource